An identification key for Chondrichthyes egg cases of the Mediterranean and Black Sea. Issue 1 (1st January 2021) - Mancusi, C.; Massi, D.; Baino, R.; Cariani, A.; Crobe, V.; Ebert, D. A.; Ferrari, A.; Gordon, C. A.; Hoff, G. R.; Iglesias, S. P.; Titone, A.; Serena, F.
Abstract: Chondrichthyan egg cases are important elements for species-specific identification and also provide a valuable aid in determining a species spatial distribution, as well as for defining spawning areas. Considering the absence of a general key for the identification of the egg cases of the Mediterranean Chondrichthyes, this work aims to fill this gap by presenting a species-specific key based on morphological features of the egg case. The key was developed primarily analysing fresh egg cases dissected from the oviduct, egg cases collected from the seabed or found dried lying on the seashore, after species confirmation by DNA analysis. Original data were integrated with information scrutinized from literature. In order to improve species identification, a protocol for the standardized acquisition of morpho-biometric and meristic features is also provided as a pre-requisite for the appropriate use of the identification key. The total width and length included the horns, when they are not broken, are the parameters that best explain the assignment of the egg case to a specific species.